2015
DOI: 10.1002/ase.1549
|View full text |Cite
|
Sign up to set email alerts
|

Medical student preferences for self‐directed study resources in gross anatomy

Abstract: Gross anatomy instruction in medical curricula involve a range of resources and activities including dissection, prosected specimens, anatomical models, radiological images, surface anatomy, textbooks, atlases, and computer-assisted learning (CAL). These resources and activities are underpinned by the expectation that students will actively engage in self-directed study (SDS) to enhance their knowledge and understanding of anatomy. To gain insight into preclinical versus clinical medical students' preferences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 39 publications
5
69
1
2
Order By: Relevance
“…This is an impressive result for the LAHFS, given that participants used it for only once for 10-15 minutes. The rank order of other resources were similar to rankings in other studies (Choi-Lundberg et al, 2015;Azer and Eizenberg, 2007;Kerby et al, 2011;Zurada et al, 2011;Johnson et al, 2013). To achieve a middle-ranking position in such fleeting circumstances implies the LAHFS has the potential to become even more highly favoured.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This is an impressive result for the LAHFS, given that participants used it for only once for 10-15 minutes. The rank order of other resources were similar to rankings in other studies (Choi-Lundberg et al, 2015;Azer and Eizenberg, 2007;Kerby et al, 2011;Zurada et al, 2011;Johnson et al, 2013). To achieve a middle-ranking position in such fleeting circumstances implies the LAHFS has the potential to become even more highly favoured.…”
Section: Discussionsupporting
confidence: 75%
“…Providing and recommending a wide variety of learning resources, to suit learners with diverse learning preferences, may help students gain a variety of perspectives, integrate information from several learning resources, and extend their own learning approaches (Azer et al, 2013;Choi-Lundberg et al, 2015). In the present study, as well as data from over 140,000 respondents on the VARK website, the kinaesthetic responses are the most frequent at 29% compared to 22-26% for V, A, and R (VARK Learn Limited, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are not contradictory. Undoubtedly, medical imaging inserted in the course of anatomy could lead to stimulate and support the understanding of gross anatomy by teaching the anatomy from two perspectives and by reinforcing the clinical relevance of anatomy, but it is, at least in part, an inadequate tool for the self-study (Chapman 2013;Choi-Lundberg 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The favorability of lectures is often overwhelming, with students often agreeing that they were more beneficial than self-directed learning (Davis et al, 2014). Despite the push for more active modes of learning, these responses have shown that more traditional modes of delivery cannot be entirely ignored when developing curricula in anatomy and physiology (Choi-Lundberg, Low, Patman, Turner, & Sinha, 2016;Minhas, Ghosh, & Swanzy, 2012). Furthermore, it should be acknowledged that no singular approach (lectures, dissection/prosection, models, technology or living anatomy) fulfills all teaching objectives, thus a multimodal approach is best (Kerby et al, 2011).…”
Section: Traditional Approachesmentioning
confidence: 99%